The impact of cigarette smoke as a risk factor for hypertension in pregnancy - Trimaya Cahya Mulat; Jianing Wang; Asridawati Akib (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Hypertension in pregnancy is one of the severe complications and is the leading cause of maternal and perinatal morbidity and mortality. Risk factors for hypertension in pregnancy include various aspects, including exposure to cigarette smoke, which has a detrimental impact on the mother and fetus. This study aims to analyze the impact of exposure to cigarette smoke as a risk factor for hypertension in pregnancy. Methods: The design of observational analytical research with a cross-sectional design uses point-time, observation, or data collection methods to examine the relationship dynamics between impact risk factors. The dependent variable of this study is the prevalence of hypertension in pregnant women. The number of samples was 128 people using the purposive sampling technique. Results: The results of the study showed that pregnant women who were exposed to cigarette smoke, both active and passive, had a higher risk of developing hypertension compared to mothers who were not exposed. Harmful components in cigarette smoke, such as nicotine and carbon monoxide, play a role in raising blood pressure through vasoconstriction mechanisms and oxidative stress, which aggravate the workload of the heart and circulatory system. Conclusions: These findings show the need for prevention and education efforts to reduce exposure to cigarette smoke in pregnant women, to reduce the incidence of hypertension in pregnancy, and improve the health of mothers and babies. With this information, it is hoped that health workers and the public can be more aware of the dangers of cigarette smoke during pregnancy and strive for a smoke-free environment for pregnant women.